Improving waterproof/breathable performance of electrospun poly(vinylidene fluoride) fibrous membranes by thermo‐pressing. Issue 1 (31st October 2017) - Li, Xiang; Lin, Jinyou; Bian, Fenggang; Zeng, Yongchun
ABSTRACT: Facing the ever‐increasing demand for waterproof/breathable materials, a rapid and efficient fabrication method of these functional materials with excellent performance as well as robust mechanical properties remains challenging. Herein, a simple and scalable strategy referred to as thermo‐pressing is introduced to improve the waterproof/breathable performance and mechanical properties of electrospun PVDF fibrous membranes. The synergistic effect of temperature and pressure acted on the electrospun PVDF membranes on the fiber morphology and crystal structure was investigated, which can be able to effectively enhance waterproof performance and mechanical properties, endowing the as‐prepared membranes with a modest breathability. The membranes thermo‐pressed at 150 °C with a pressure of 8.27 MPa exhibit robust tensile strength of 40.65 MPa, which is superior to those of the previous reports (below 32.8 MPa). Notably, the optimized membranes enable to show a high hydrostatic pressure of 102 kPa, good WVTR of 10.87 kg m −2 d −1 and excellent abrasion resistance, which implies that the thermo‐pressing is an efficient and facile way to steer the fiber morphology and crystal structure of electrospun membranes to improve their application performance. © 2017 Wiley Periodicals, Inc. J. Polym. Sci., Part B: Polym. Phys.2018, 56, 36–45 Abstract : The electrospun PVDF fibrous membranes are thermo‐pressed when adjusting temperature and pressure simultaneously. Due to adhesive structure, optimized pore size and high porosity of the as‐prepared membranes, mechanical properties and waterproof performance of the electrospun PVDF membranes are improved effectively. In addition, the thermo‐pressed membranes maintain a modest breathability.